Listen to the voice of the customer – First steps towards stakeholder democracy - Laura Marie Edinger-Schons; Lars Lengler-Graiff; Sabrina Scheidler; Gina Mende; Jan Wieseke (Business Ethics: A European Review, 2019)
Recently, calls have grown louder for more stakeholder democracy that is, letting stakeholders participate in the process of organizing, decision-making, and governance in corporations, especially in the area of Corporate Social Responsibility (CSR) activities. Despite the relevance of the subject, the impact of customer involvement in CSR on their company-related attitudes and behaviors still represents a major research void. The paper at hand develops a conceptual framework of consumer involvement in CSR based on the existing literature, theories of stakeholder democracy, and organizational boundaries as well as drawing from the qualitative focus group interviews (N~=~24). The framework is tested on a large scale, two-time point field-experimental study (N~=~3,397). More specifically, consumer reactions to three degrees of customer involvement (i.e., information, feedback, and dialogue) are tested in two different CSR domains (i.e., company-internal business process vs. company-external philanthropic CSR). Results indicate that the customer involvement in CSR has a more beneficial effect in terms of strengthening customer outcomes in CSR domains that directly affect external stakeholders of the company (i.e., philanthropic CSR) than in domains that mainly concern company-internal stakeholders (i.e., business process CSR).
Keywords: 330